2015
DOI: 10.1016/j.ajog.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bipolar electrocoagulation during ovarian cystectomy on ovarian reserve: a systematic review

Abstract: The aim of the present systematic review was to study the effect of bipolar electrocoagulation during ovarian cystectomy on ovarian reserve. We searched Medline (1966-2015), Scopus (2004-2015), ClinicalTrials.gov (2008-2015), and Cochrane Central Register (CENTRAL) databases along with reference lists of electronically retrieved studies. The levels of antimullerian hormone (AMH) and antral follicle count (AFC) at 1, 3, 6, and 12 months following the excision of the benign ovarian cyst were defined as primary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 23 publications
3
14
1
2
Order By: Relevance
“…In contrast to previous publications, we found that the ovarian reserve as measured by AFC had improved following endometrioma surgery; however, have been a few publications which observed that the ovarian reserve may indeed improve following surgery . We think the most likely explanation for the controversies reported is the amount of injury inflicted on the ovary during the operation, which may consist of mechanical, vascular, and thermal injuries.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…In contrast to previous publications, we found that the ovarian reserve as measured by AFC had improved following endometrioma surgery; however, have been a few publications which observed that the ovarian reserve may indeed improve following surgery . We think the most likely explanation for the controversies reported is the amount of injury inflicted on the ovary during the operation, which may consist of mechanical, vascular, and thermal injuries.…”
Section: Discussioncontrasting
confidence: 95%
“…Laparoscopic cystectomy using the stripping method is the most commonly adopted operative technique, but it has been shown to reduce the ovarian reserve . Moreover, haemostasis using bipolar coagulation on the residual ovarian tissue may further damage the ovarian reserve …”
Section: Introductionmentioning
confidence: 99%
“…При необходимости остановки кровотечения используются различные виды гемостаза. На данном этапе развития медицины многими учеными с позиции сохранения овариального резерва (ОР), обеспечения быстрого восстановления архитектоники оперированной гонады исследуются различные методы остановки кровотечения (биполярная, аргоноплазменная, ультразвуковая коагуляция, лигатурный гемостаз -ЛГ) [5][6][7][8][9][10][11][12].…”
Section: российский вестник акушера-гинеколога 2 2017unclassified
“…В качестве рутинного метода гемостаза используется биполярная коагуляция (БПК). Накоплен большой опыт по изучению влияния данного вида энергии на овариальную ткань при энуклеации эндометриоидных образований яичников (ЭОЯ) [1,2,5,[9][10][11].…”
Section: российский вестник акушера-гинеколога 2 2017unclassified
“…Laparoscopic ovarian cystectomy is established as the gold standard surgical approach to the ovarian benign cyst [3]. However, some previous studies have shown that potential fertility can be directly impaired by laparoscopic ovarian cystectomy [4][5][6], and diminished ovarian reserve (DOR) and even premature ovarian failure [7][8][9], respectively. Many previous researches have con rmed the ovarian reserve damage after the laparoscopic stripping of endometrioma [10][11][12][13][14][15].Those who had undergone laparoscopic cystectomy for endometrioma showed lower AMH levels than the healthy women without ovarian cysts (4.2 ± 2.3 vs. 2.8 ± 2.2 ng/ml; P = 0.02), and also AFC lower levels (14.7 ± 4.1 vs. 9.7 ± 4.8 ng/ml; P < 0.01) [11].The decline rate of AMH levels was signi cantly greater in the bipolar coagulation group than in the suture group during laparoendoscopic single-site cystectomy for ovarian endometriomas (42.2 % vs 24.6 %, P = 0.001) [13].…”
Section: Introductionmentioning
confidence: 99%